2002
DOI: 10.1002/ffj.1095
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and isolation of Pistacia lentiscus L. essential oil by supercritical CO2

Abstract: Supercritical CO 2 extraction coupled to a fractional separation technique (SFE) was used to isolate essential oil from the leaves and berries of Pistacia lentiscus L. The technique adopted allowed us to separate the volatile oil from waxes. In the case of the leaf essential oil, the yield was 0.45% by weight of the charged material. The chemical composition of the oil, determined by GC-MS analysis, revealed the presence ofˇ-caryophyllene (31.38%), germacrene D (12.05%) and -cadinene (6.48%). Remarkable differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 10 publications
(8 reference statements)
5
31
4
Order By: Relevance
“…In our study terpinene-4-ol was by far the major component (41.24%) accompanied [9] and 31.5% Italy [20].…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In our study terpinene-4-ol was by far the major component (41.24%) accompanied [9] and 31.5% Italy [20].…”
Section: Discussionsupporting
confidence: 46%
“…In other countries of the Mediterranean region, several studies have been studied the chemical composition of P. lentiscus L. oil [6]- [20] and several compositions were observed. Myrcene (39.2%), which is the major compounds of our essential oil, has also the abundant compound in the samples from Morocco (38%) [4], France (76.9%) [6], Spain (27%) [7], Italy (25.2%) [8] and Algeria (23.0% -33.1%) [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous studies [22][23] we chose the following extraction conditions: 90 bar and 50°C (density of carbon dioxide, ρCO 2 = 0.287 g/cm 3 ). These conditions allowed the extraction of volatile oil without undesired compounds, except waxes, for both treated materials.…”
Section: Resultsmentioning
confidence: 99%
“…An essential oil has been isolated from P. lentiscus by supercritical CO 2 . 7 Many authors have found that the P. lentiscus essential oil has interesting antibacterial and antimicrobial activity. 8,9 Marone et al, 10 evaluating the antibacterial activity of P. lentiscus mastic gum against Helicobacter pylori, have found that the mastic gum has a very interesting activity.…”
Section: Introductionmentioning
confidence: 99%